New insights into the peroxisomal protein inventory: Acyl-CoA oxidases and -dehydrogenases are an ancient feature of peroxisomes - Camões, Fátima; Islinger, Markus (Biochimica et biophysica acta. Molecular cell research, 2015)
Peroxisomes are ubiquitous organelles which participate in a variety of essential biochemical pathways. An intimate interrelationship between peroxisomes and mitochondria is emerging in mammals, where both organelles cooperate in fatty acid β-oxidation and cellular lipid homeostasis. As mitochondrial fatty acid β-oxidation is lacking in yeast and plants, suitable genetically accessible model systems to study this interrelationship are scarce. Here, we propose the filamentous fungus Ustilago maydis as a suitable model for those studies. We combined molecular cell biology, bioinformatics and phylogenetic analyses and provide the first comprehensive inventory of U. maydis peroxisomal proteins and pathways. Studies with a peroxisome-deficient Δpex3 mutant revealed the existence of parallel and complex, cooperative β-oxidation pathways in peroxisomes and mitochondria, mimicking the situation in mammals. Furthermore, we provide evidence that acyl-CoA dehydrogenases (ACADs) are bona fide peroxisomal proteins in fungi and mammals and together with acyl-CoA oxidases (ACOX) belong to the basic enzymatic repertoire of peroxisomes. A genome comparison with baker's yeast and human gained new insights into the basic peroxisomal protein inventory shared by humans and fungi and revealed novel peroxisomal proteins and functions in U. maydis. The importance of our findings for the evolution and function of the complex interrelationship between peroxisomes and mitochondria in fatty acid β-oxidation is discussed.